A Note on Existence of Global Solutions for Impulsive Functional Integrodifferential Systems - Dineshkumar, C.; Udhayakumar, R. (Discontinuity, Nonlinearity, and Complexity, 2026)
In our manuscript, we research the existence of global solutions for a class of impulsive abstract functional integrodifferential systems with nonlocal conditions. We proved our outcomes by utilizing the Leray-Schauder’s Alternative fixed point theorem. Lastly, a model is presented for illustration of theory.